-7b-7(3b+4)=

Simple and best practice solution for -7b-7(3b+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7b-7(3b+4)= equation:


Simplifying
-7b + -7(3b + 4) = 0

Reorder the terms:
-7b + -7(4 + 3b) = 0
-7b + (4 * -7 + 3b * -7) = 0
-7b + (-28 + -21b) = 0

Reorder the terms:
-28 + -7b + -21b = 0

Combine like terms: -7b + -21b = -28b
-28 + -28b = 0

Solving
-28 + -28b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '28' to each side of the equation.
-28 + 28 + -28b = 0 + 28

Combine like terms: -28 + 28 = 0
0 + -28b = 0 + 28
-28b = 0 + 28

Combine like terms: 0 + 28 = 28
-28b = 28

Divide each side by '-28'.
b = -1

Simplifying
b = -1

See similar equations:

| (x/4)^20 | | f(x)=Log(4x+12) | | 2-10=x/-7 | | 2a-4b+3b+3a= | | 3a^5-39a^3+108a=0 | | 4a-2x+7a-x= | | 2y=-13(x-5) | | 2x-3y+x-4y= | | 3x-5y-(-3x)= | | 3a+b-(-2b)= | | 4a-5c+3a-c= | | 2a+3x-4x-5a= | | 9+b=c+3a | | -2(x-1)=-2x-(x+4) | | 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= |

Equations solver categories